Spatial-Temporal Analysis of Particulate Matter (PM10) and Sulphur Dioxide (SO2) Concentrations in Ankara Using Climate Parameters - Olgu Aydın; Nussaïbah Begum Raja (Doğal Afetler ve Çevre Dergisi)
Air pollution in Turkey has become a significant issue, particularly in large cities, due to population growth, unplanned urbanization, and increases in industrial and energy facilities. Particulate Matter (PM10) and Sulphur Dioxide (SO2) concentrations significantly deteriorate air quality due to high emissions from industrial and energy production. Ankara, one of the major cities facing air pollution problems, is noted as having air pollution among the top issues in the 2022 Turkey Environmental Issues and Priorities Assessment Report. This study aims to investigate the spatial-temporal changes in PM10 and SO2 concentrations in Ankara from 2011 to 2014 under the influence of meteorological factors using the Kriging with External Drift (KED) method. In 2011, PM10 and SO2 concentration levels were lower compared to other years but remained above the annual concentration limits set by the World Health Organization (WHO). In 2012 and 2013, increases in PM10 and SO2 concentrations were observed, showing variability across different regions of the city. In 2014, a notable decrease in PM10 and SO2 concentrations was observed, coinciding with increased rainfall and temperature values. When evaluating the performance of the prediction models for PM10 and SO2 concentrations, it is found that the PM10 model explains 66% and the SO2 model explains 78% of the variance. The spatial-temporal KED analysis of PM10 and SO2 concentrations using meteorological factors is crucial for understanding the changes in air pollution and comprehending the relationships between spatial variables and their interactions over time.